The Effect of CSR on Firm Performance: The Moderating Role of the Audit Committee in Basic Material Companies on the Indonesian Stock Exchange for the Period 2021-2023 - Amatul Mu’min; Dina Enjellina; Acep Komara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to analyze the influence of Corporate Social Responsibility (CSR) on company performance, with the audit committee acting as a moderating variable, specifically in the basic materials sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. Employing a quantitative approach, the study focuses on non-financial companies and uses purposive sampling to obtain 87 samples. Data are sourced from annual and sustainability reports and are analyzed using Moderated Regression Analysis (MRA) to evaluate both the direct impact of CSR and the moderating role of the audit committee in the CSR-performance relationship. The findings indicate that the presence of an audit committee enhances the positive relationship between CSR and company performance.